Reduire chaque expression
A=3*t+(2*tau carré +9)-(-9*t+t au carré
B=u-(11-u au carré) + (12*u-3)
C=-2*yau carré-(3*y-6*yau carré+(-5*y+9)
D=7*z+(5*zau carré-5*z)-(2*z-3)

Reduire chaque expression

A=3*p-(2*p au carre-5 *p+3)+2-(6*t au carré -3*t-12)

B=-(3*t+9*t au carré-3)+2-(6*t au carré-3*t-12)

C=3*m+(-5*m au carré-3+12*m)-(-2*m+3-6*m au carré)

D=-(11*a au carré-3*a+5)+3*a-(12*a-3*a au carré+9)

*multiplication

SVPPPPPPPPPPPPP AIDEZ MOI C EST POUR DEEMAIN SVPPPPPPPPPPPPPPPPPPPPPPPPPPPPPPPPPPPPPPPPP

1

Réponses

2014-03-10T19:19:10+01:00

Réduire chaque expression:


A= 3xt + (2t² + 9) - (-9t + t²)

A= 3t + 2t² + 9 + 9t - t²

A= 2t² - t² + 3t + 9t + 9

A= t² + 12t + 9


B= u - (11 - u²) + (12 x u - 3)

B= u - 11 + u² + 12u - 3

B= u² + 12u + u - 11 - 3

B= u² + 13u - 13


C= -2 x y² - (3 x y - 6 x y² + (-5 x y + 9)

C= -2y² - 3y + 6y² - 5y + 9

C= -2y² + 6y² - 3y - 5y + 9

C= 4y² - 8y + 9


D= 7 x z + (5 x z² - 5 x z) - (2 x z - 3)

D= 7z + 5z² - 5z - 2z + 3

D= 5z² + 7z - 5z - 2z + 3

D= 5z² + 3


A= 3 x p - (2 x p² - 5 x p + 3) + 2 - (6 x t² - 3 x t - 12)

A= 3p - 2p² + 5p - 3 + 2 - 6t² + 3t + 12

A= -2p² - 6t² + 3p + 5p + 3t - 3 + 2 + 12

A= -2p² - 6t² + 8p + 3t + 11


B= -(3 x t + 9 x t² - 3) + 2 - (6 x t² - 3 x t - 12)

B= -3t - 9t² + 3 + 2 - 6t² + 3t + 12

B= -9t² - 6t² - 3t + 3t + 3 + 2 + 12

B= -15t² + 0t + 17

B= -15t² + 17


C= 3 x m + (5 x m² - 3 + 12 x m) - (-2 x m + 3 - 6 x m²)

C= 3m + 5m² - 3 + 12m + 2m - 3 + 6m²

C= 5m² + 6m² + 3m + 12m + 2m - 3 - 3

C= 11m² + 17m - 6


D= - (11 x a² - 3 x a - (12 x a - 3 x a² + 9)

D= - 11a² + 3a - 12a + 3a² - 9

D= -11a² + 3a² + 3a - 12a - 9

D= -8a²- 9a - 9